Experimental Study of a Phase-Change Thermoacoustic Engine for Maritime Waste Heat Recovery System - Korobko Volodymyr; Shevtsov Anatoliy; Serbin Serhiy; Wen Huabing; Dzida Marek (Polish Maritime Research)
Efforts to lower the temperature of waste heat from engines in industry, transportation, and power generation have gained significant attention. Due to the low exergy potential of such emissions, utilising these low-temperature heat sources with conventional engines remains a challenge. Improving existing technologies or developing new solutions is critical. For example, in modern marine 2-stroke and 4-stroke engines, cooling coolant temperatures range from 353–365 K, while liquid heat emissions to the environment typically do not exceed 320 K. Thermoacoustic technologies offer a promising approach. Thermoacoustic engines (TAEs) can harness low-temperature (LT) external heat sources to generate mechanical work. Interestingly, thermoacoustic oscillations have been observed with small temperature differences between heat sources, particularly in humid environments. This phenomenon could enable the development of LT energy-saving systems using TAEs in a two-phase working medium. However, applying thermoacoustic systems in maritime settings requires further research, particularly to improve the specific power of TAEs. This paper presents experimental results on TAEs operating with a wet working medium. Experiments have shown that in a TAE with a ‘wet’ medium based on air and water, thermoacoustic oscillations arise at 355–359 K with a temperature gradient in the matrix of 1.19–1.30 K/mm, leading to a 1.7–7-fold increase in the TAE’s acoustic power. It was also found that, under the research conditions, the droplet condensation of water vapour can occur in the ceramic matrix and on the surfaces of the TAE heat exchangers, potentially affecting the overall efficiency of energy conversion processes.